Preparation method of acid / alkali bipolar electrolyzed water catalyst with high-stability multi-element rutile structure

By introducing acid-resistant and alkali-resistant elements into the electrolytic water hydrogen production catalyst, a high-stable multivariate rutile structure is formed, which solves the stability of the catalyst under different conditions, and achieves cost reduction and performance improvement.

CN119465240AActive Publication Date: 2025-02-18HEFEI UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411645800.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

In the existing electrolytic hydrogen production technology, the catalyst has poor stability, especially under alkaline and acidic conditions, resulting in high cost and unstable performance.

Method used

Using acid/alkali bisexual electrolytic catalyst with a high-stable multivariate rutile structure, the stability of the catalyst under different conditions is improved by introducing acid-resistant and alkali-resistant elements, and the amount of precious metals is reduced through specific preparation methods and composition optimization. .

Benefits of technology

The high stability of the catalyst under alkaline and acidic conditions is achieved, the cost of hydrogen production by electrolyzing water is reduced, the electrolytic performance is improved, and the use of precious metals is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465240A_ABST
    Figure CN119465240A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an acid / alkali bipolar electrolyzed water catalyst with a high-stability multi-element rutile structure. The catalyst comprises the following components in parts by weight: 0.1-25 parts of a non-noble metal precursor with catalytic activity, 0.1-50 parts of a noble metal precursor with catalytic activity, 1-200 parts of an acetone solution and 1-200 parts of a metal chelating agent. The method comprises the following steps: mixing a mixed solution of an acetone solution and a metal chelating agent with a mixed solution of an acetone solution and a catalytic active non-noble metal precursor a to form a mixed solution 1, adding a catalytic active non-noble metal precursor b to form a mixed solution 2, and adding the mixed solution of the catalytic active noble metal precursor and the acetone solution to form a mixed solution 3; and carrying out hydrothermal reaction on the mixed solution 3, centrifugally washing the obtained solid product with acetone, and carrying out suction filtration, drying, carbonization and calcination. A large number of acid-resistant and alkali-resistant elements are introduced, so that the stability of the catalyst under alkaline and acidic conditions is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of hydrogen production by electrolysis of water, and in particular to a method for preparing an acid / base amphoteric water electrolysis catalyst with a highly stable multi-component rutile structure. Background Art

[0002] At present, green energy represented by hydrogen energy has the characteristics of cleanliness, high efficiency, and environmental friendliness, and has a higher energy density than traditional fossil energy. At present, industrial applications are still mainly based on fossil energy hydrogen production, which obviously cannot solve the problem of fossil energy pollution to the environment. The electrolysis of water to produce hydrogen technology using water as raw material has environmentally friendly characteristics, its product is single, and the purity of hydrogen production is high. At present, electrolysis of water to produce hydrogen is mainly divided into four categories: PEM electrolysis of water, alkaline electrolysis of water (ALK), anion exchange membrane electrolysis of water (AEM) and high-temperature solid oxide electrolysis of water. Among them, alkaline electrolysis of water (ALK) technology is already quite mature, low cost, but slow dynamic response, low working current density, and high electrolyte concentration; PEM electrolysis of water has also been commercialized, with fast dynamic response and high working current density, but high cost; anion exchange membrane electrolysis of water (AEM) has high working current density, low cost, and fast dynamic response, but it is still in the experimental stage, and high-temperature solid oxide electrolysis of water has a high working temperature and is still in the experimental stage.

[0003] With the rapid development of photovoltaic power generation and wind power generation, hydrogen is one of the green energy sources with low storage cost. The over-produced electricity can be stored in the form of hydrogen by using water electrolysis hydrogen production technology. In addition, photovoltaic power generation and wind power generation are unstable and greatly affected by the environment. The electricity they generate cannot be directly used. By using the characteristics of fast dynamic response of PEM water electrolysis and AEM water electrolysis, they can be used in conjunction with photovoltaic and wind power generation systems to solve the problem of unstable power generation. However, PEM water electrolysis is expensive, one of the reasons is that it requires the precious metal iridium as a catalyst, so it is necessary to develop a low-cost catalyst; although the anode catalyst of AEM water electrolysis can use non-precious metals, its stability is poor, and a small amount of precious metals can be introduced to improve the stability of the catalyst.

[0004] The precious metal ruthenium is favored by researchers due to its low cost and high activity. In PEM water electrolysis, although ruthenium oxide shows excellent water electrolysis activity, its stability is poor, so it is necessary to improve the stability of ruthenium-based catalysts in PEM water electrolysis by doping. In AEM water electrolysis, although low-cost non-precious metal catalysts can be used, the stability of non-precious metals is still not optimistic. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing an acid / base amphoteric water electrolysis catalyst with a highly stable multi-component rutile structure, which introduces a large amount of acid-resistant and alkali-resistant elements to improve the stability of the catalyst under alkaline and acidic conditions.

[0006] In one aspect of the present invention, the present invention provides an acid / base amphoteric water electrolysis catalyst with a highly stable multi-component rutile structure. According to an embodiment of the present invention, the catalyst comprises the following components in parts by weight: 0.1 to 25 parts of a catalytically active non-precious metal precursor, 0.1 to 50 parts of a catalytically active precious metal precursor, 1 to 200 parts of an acetone solution, and 1 to 200 parts of a metal chelating agent.

[0007] In addition, the highly stable multi-component rutile acid / base amphoteric water electrolysis catalyst according to the above embodiment of the present invention may also have the following additional technical features:

[0008] In some embodiments of the present invention, the catalytically active non-precious metal precursor is a plurality of SnCl4, MnCl2, GeCl4, VCl3, WCl3 and TiCl4.

[0009] In some embodiments of the present invention, the catalytically active noble metal precursor is RuCl3 or H2IrCl6.

[0010] In some embodiments of the present invention, the metal chelator is one of phenanthroline, xanthate, dithiocarbamate derivatives, ethylenediaminetetraacetic acid, diethylenetriammonium pentaacetic acid, citric acid and hexamethylenetetraammonium.

[0011] In another aspect of the present invention, the present invention provides a method for preparing a highly stable multi-element rutile structured acid / base amphoteric water electrolysis catalyst. According to an embodiment of the present invention, the method comprises the following steps:

[0012] (1) mixing an acetone solution and a metal chelating agent (introducing a large amount of carbon source to improve the conductivity of the catalyst) to form a solution A;

[0013] (2) uniformly mixing the acetone solution and the catalytically active non-noble metal precursor a to form a solution B;

[0014] (3) Slowly adding solution B dropwise into solution A, and after ultrasonic treatment, forming a mixed solution 1;

[0015] (4) adding one or more catalytically active non-noble metal precursors b into the mixed solution 1 and stirring to form a mixed solution 2, wherein the catalytically active non-noble metal precursor a and the catalytically active non-noble metal precursor b are different substances in the catalytically active non-noble metal precursor;

[0016] (5) dissolving a catalytically active noble metal precursor in an acetone solution and stirring the solution to form a solution C;

[0017] (6) slowly adding the mixed solution 2 dropwise to the solution C, and after ultrasonic treatment, forming a mixed solution 3;

[0018] (7) Adding the mixed solution 3 into a reaction kettle to carry out a hydrothermal reaction;

[0019] (8) washing the solid product obtained in step (7) by centrifugation with acetone, and then filtering and drying;

[0020] (9) Grinding the solid product obtained in step (8) into fine powder, and then reducing and carbonizing it in a tube furnace (to improve the conductivity and stability of the catalyst);

[0021] (10) Grinding the product obtained in step (9) into fine powder, and calcining at low temperature (ensuring that the surface of the catalyst nanoparticles is partially oxidized but the inside is not oxidized, thereby improving its conductivity) to obtain the acid / base amphoteric water electrolysis catalyst with a highly stable multi-component rutile structure.

[0022] In addition, the method for preparing a highly stable multi-element rutile structured acid / base amphoteric water electrolysis catalyst according to the above embodiment of the present invention may also have the following additional technical features:

[0023] In some embodiments of the present invention, in step (3) and step (6), the ultrasonic time is 30 to 60 minutes; in step (4), the stirring time is 10 to 30 minutes.

[0024] In some embodiments of the present invention, in step (7), the temperature of the hydrothermal reaction is 110 to 180° C., and the time of the hydrothermal reaction is 15 to 24 hours.

[0025] In some embodiments of the present invention, in step (8), the drying temperature is 40-80°C.

[0026] In some embodiments of the present invention, in step (9), the temperature of the tube furnace is 850-900°C.

[0027] In some embodiments of the present invention, in step (10), the calcination temperature is 200-300° C., and the calcination time is 30-60 min.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1) The present invention can not only improve the performance of Ru by changing the electron cloud arrangement around Ru, but also inhibit Ru from being oxidized to high-valent ruthenium and precipitating, causing a sharp decline in performance.

[0030] 2) The membrane electrode prepared by the present invention using a catalyst of a polyvalent acid-resistant and highly stable rutile structure has good stability in PEM water electrolysis and AEM water electrolysis, and can also reduce the amount of precious metal ruthenium used and reduce the cost of water electrolysis.

[0031] 3) A large amount of non-precious metal elements are introduced into the catalyst prepared by the present invention, which reduces the amount of precious metals used and effectively reduces the cost of the electrolytic cell.

[0032] 4) A large amount of acid-resistant and alkaline-resistant elements are introduced into the catalyst prepared by the present invention, thereby improving the stability of the catalyst under alkaline and acidic conditions.

[0033] 5) Two or more non-precious metal elements are introduced into the catalyst prepared by the present invention, and the interaction between the non-precious metal elements and the precious metal elements is utilized to improve the electrolysis performance of the catalyst under alkaline and acidic conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is RuMnSnO in Example 1 of the present invention x The electrolysis performance diagram of the full cell in PEM water electrolysis;

[0035] Figure 2 is RuMnSnO in Example 1 of the present invention x Stability of the full cell in PEM water electrolysis.

[0036] Figure 3 is RuMnSnO in Example 1 of the present invention x Graph showing the electrolysis performance of the full cell in AEM water electrolysis.

[0037] Figure 4 is RuMnSnO in Example 1 of the present invention x Electrical stability of the full cell in AEM water electrolysis.

[0038] Figure 5 is RuMnSnO in Example 1 of the present invention x XRD pattern with characteristic peaks of rutile structure. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1

[0041] A highly stable multi-component rutile structured acid / base bipolar water electrolysis catalyst comprises the following raw materials: 60 ml of acetone, 260 mg of a catalyst-active noble metal precursor RuCl3, 80 mg of a catalytically active non-noble metal precursor a SnCl4, 38 mg of a catalytically active non-noble metal precursor b MnCl2, and 0.6 g of phenanthroline.

[0042] A method for preparing a highly stable multi-element rutile structured acid / base amphoteric water electrolysis catalyst comprises the following steps:

[0043] Step 1: Measure 20 ml of acetone solution and pour it into beaker 1, then weigh 0.6 g of phenanthroline and pour it into beaker 1, and stir evenly to form a uniform solution A.

[0044] Step 2: Measure 20 ml of acetone solution and pour it into beaker 2, then add 80 mg of SnCl4 dropwise therein, stir evenly, and form a uniform solution B.

[0045] Step 3: Slowly add solution B obtained in step 2 to solution A obtained in step 1 to form a mixed solution 1, and perform ultrasound for 30 minutes.

[0046] Step 4: Weigh 38 mg of MnCl2 and add it to mixed solution 1, and stir for 10 minutes to form mixed solution 2.

[0047] Step 5: Weigh 260 mg of RuCl3 and dissolve it in 30 ml of acetone solution, and stir evenly to form a uniform solution C.

[0048] Step 6: Slowly drop the mixed solution 2 obtained in step 4 into the uniform solution C obtained in step 5, and perform ultrasound for 30 minutes to form a mixed solution 3.

[0049] Step 7: The mixed solution 3 obtained in step 6 is placed in a reactor and hydroheated at 110° C. for 20 h.

[0050] Step 8: The solid product obtained in step 7 was washed 4 times by centrifugation with acetone, then filtered and dried at 60°C.

[0051] Step 9: Grind the solid product obtained in step 8 into fine powder, and then place it in a tube furnace at 900° C. for reduction and carbonization.

[0052] Step 10: Grind the above product into fine powder, place it in a muffle furnace and calcine it at 300°C for 60 minutes to obtain RuMnSnOx catalyst.

[0053] PEM water electrolysis performance test: weigh 100 mg of RuMnSnO xPrepare slurry as anode catalyst, weigh 100 mg of Pt / C and prepare slurry as cathode catalyst, the anode catalyst equivalent is 2 mg / cm 2 , the cathode catalyst equivalent is 0.3mg / cm 2 The catalyst prepared above is made into a membrane electrode, and deionized water is introduced into the anode and cathode respectively. A suitable gradient voltage is applied to the electrolytic cell, such as Figure 1 As shown, based on RuMnSnO x The electrolytic cell made of catalyst was operated at a current density of 2A·cm -2 When the voltage is only 2V, it can -2 It can operate stably for at least 50h at a current density of Figure 2 Although pure water is fed into the PEM electrolysis water, the reaction process will produce H + , which is an acidic state, indicating that RuMnSnOx is stable under acidic conditions.

[0054] AEM water electrolysis performance test: weigh 100 mg of RuMnSnO x Prepare a slurry as the anode catalyst. Similarly, weigh 100 mg of Pt / C and prepare a slurry as the cathode catalyst. The anode catalyst equivalent is 6 mg / cm 2 , the cathode catalyst equivalent is 0.3mg / cm 2 The catalyst prepared above was made into a membrane electrode, 1 mol KOH solution was introduced into the anode and cathode respectively, and a suitable gradient voltage was applied to the electrolytic cell. Figure 3 As shown, based on RuMnSnO x The electrolytic cell made of catalyst can reach a current density of 1.4A·cm at a current density of 2V. -2 . And can be at 0.5A·cm -2 It can run stably for at least 22h at a current density of Figure 4 In addition, Figure 5 It shows that RuMnSnO x It has the same rutile structure characteristic peak as RuO2, indicating that RuMnSnO x It is a rutile structure catalyst with high and stable water electrolysis ability.

[0055] Example 2

[0056] A highly stable multi-component rutile structured acid / base bipolar water electrolysis catalyst comprises the following raw materials: 60 ml of acetone, 260 mg of a catalyst-active noble metal precursor RuCl3, 85 mg of a catalytically active non-noble metal precursor a TiCl4, 38 mg of a catalytically active non-noble metal precursor b MnCl2, and 0.6 g of phenanthroline.

[0057] A method for preparing a highly stable multi-element rutile structured acid / base amphoteric water electrolysis catalyst comprises the following steps:

[0058] Step 1: Measure 20 ml of acetone solution and pour it into beaker 1, then weigh 0.6 g of phenanthroline and pour it into beaker 1, and stir evenly to form a uniform solution A.

[0059] Step 2: Measure 20 ml of acetone solution and pour it into beaker 2, then add 85 mg of TiCl4 dropwise therein, stir evenly, and form a uniform solution B.

[0060] Step 3: Slowly add solution B obtained in step 2 to solution A obtained in step 1 to form a mixed solution 1, and perform ultrasound for 30 minutes.

[0061] Step 4: Weigh 38 mg of MnCl2 and add it to mixed solution 1, and stir for 10 minutes to form mixed solution 2.

[0062] Step 5: Weigh 260 mg of RuCl3 and dissolve it in 30 ml of acetone solution, and stir evenly to form a uniform solution C.

[0063] Step 6: Slowly drop the mixed solution 2 obtained in step 4 into the uniform solution C obtained in step 5, and perform ultrasound for 30 minutes to form a mixed solution 3.

[0064] Step 7: The mixed solution 3 obtained in step 6 is placed into a reactor and hydroheated at 110° C. for 20 h.

[0065] Step 8: The solid product obtained in step 7 was washed 4 times by centrifugation with acetone, then filtered and dried at 60°C.

[0066] Step 9: Grind the solid product obtained in step 8 into fine powder, and then place it in a tube furnace at 900° C. for reduction and carbonization.

[0067] Step 10: Grind the above product into fine powder, place it in a muffle furnace and calcine it at 300°C for 60 minutes to obtain the RuMnTiOx catalyst.

[0068] PEM water electrolysis performance test: weigh 100 mg of RuMnTiO x Prepare a slurry as the anode catalyst. Similarly, weigh 100 mg of Pt / C and prepare a slurry as the cathode catalyst. The anode catalyst equivalent is 2 mg / cm 2 , the cathode catalyst equivalent is 0.3mg / cm 2 The catalyst prepared above is made into a membrane electrode, deionized water is introduced into the anode and cathode respectively, and a suitable gradient voltage is applied to the electrolytic cell.

[0069] AEM water electrolysis performance test: weigh 100 mg of RuMnTiO x Prepare a slurry as the anode catalyst. Similarly, weigh 100 mg of Pt / C and prepare a slurry as the cathode catalyst. The anode catalyst equivalent is 6 mg / cm 2 , the cathode catalyst equivalent is 0.3mg / cm 2 The catalyst prepared above was made into a membrane electrode, 1 mol KOH solution was introduced into the anode and cathode respectively, and a suitable gradient voltage was applied to the electrolytic cell.

[0070] Example 3

[0071] A highly stable multi-component rutile structured acid / base bipolar water electrolysis catalyst comprises the following raw materials: 60 ml of acetone, 260 mg of a catalyst-active noble metal precursor RuCl3, 80 mg of a catalytically active non-noble metal precursor a SnCl4, 85 mg of a catalytically active non-noble metal precursor b TiCl4, and 0.6 g of phenanthroline.

[0072] A method for preparing a highly stable multi-element rutile structured acid / base amphoteric water electrolysis catalyst comprises the following steps:

[0073] Step 1: Measure 20 ml of acetone solution and pour it into beaker 1, then weigh 0.6 g of phenanthroline and pour it into beaker 1, and stir evenly to form a uniform solution A.

[0074] Step 2: Measure 20 ml of acetone solution and pour it into beaker 2, then add 80 mg of SnCl4 dropwise therein, stir evenly, and form a uniform solution B.

[0075] Step 3: Slowly add solution B obtained in step 2 to solution A obtained in step 1 to form a mixed solution 1, and perform ultrasound for 30 minutes.

[0076] Step 4: Weigh 85 mg of TiCl4 and add it to mixed solution 1, and stir for 10 minutes to form mixed solution 2.

[0077] Step 5: Weigh 260 mg of RuCl3 and dissolve it in 30 ml of acetone solution, and stir evenly to form a uniform solution C.

[0078] Step 6: Slowly drop the mixed solution 2 obtained in step 4 into the uniform solution C obtained in step 5, and perform ultrasound for 30 minutes to form a mixed solution 3.

[0079] Step 7: The mixed solution 3 obtained in step 6 is placed into a reactor and hydroheated at 110° C. for 20 h.

[0080] Step 8: The solid product obtained in step 7 was washed 4 times by centrifugation with acetone, then filtered and dried at 60°C.

[0081] Step 9: Grind the solid product obtained in step 8 into fine powder, and then place it in a tube furnace at 900° C. for reduction and carbonization.

[0082] Step 10: Grind the above product into fine powder, place it in a muffle furnace and calcine it at 300°C for 60 minutes to obtain RuTiSnOx catalyst.

[0083] PEM water electrolysis performance test: weigh 100 mg of RuTiSnO x Prepare a slurry as the anode catalyst. Similarly, weigh 100 mg of Pt / C and prepare a slurry as the cathode catalyst. The anode catalyst equivalent is 2 mg / cm 2 , the cathode catalyst equivalent is 0.3mg / cm 2 The catalyst prepared above is made into a membrane electrode, deionized water is introduced into the anode and cathode respectively, and a suitable gradient voltage is applied to the electrolytic cell.

[0084] AEM water electrolysis performance test: weigh 100 mg of RuTiSnO x Prepare a slurry as the anode catalyst. Similarly, weigh 100 mg of Pt / C and prepare a slurry as the cathode catalyst. The anode catalyst equivalent is 6 mg / cm 2 , the cathode catalyst equivalent is 0.3mg / cm 2 The catalyst prepared above was made into a membrane electrode, 1 mol KOH solution was introduced into the anode and cathode respectively, and a suitable gradient voltage was applied to the electrolytic cell.

[0085] Example 4

[0086] A highly stable multi-component rutile structured acid / base bipolar water electrolysis catalyst comprises the following raw materials: 60 ml of acetone, 260 mg of a catalytically active noble metal driver RuCl3, 80 mg of a catalytically active non-noble metal precursor a SnCl4, 85 mg of a catalytically active non-noble metal precursor b TiCl4, 38 mg of MnCl2, and 0.6 g of phenanthroline.

[0087] A method for preparing a highly stable multi-element rutile structured acid / base amphoteric water electrolysis catalyst comprises the following steps:

[0088] Step 1: Measure 20 ml of acetone solution and pour it into beaker 1, then weigh 0.6 g of phenanthroline and pour it into beaker 1, and stir evenly to form a uniform solution A.

[0089] Step 2: Measure 20 ml of acetone solution and pour it into beaker 2, then add 80 mg of SnCl4 dropwise therein, stir evenly, and form a uniform solution B.

[0090] Step 3: Slowly add solution B obtained in step 2 to solution A obtained in step 1 to form a mixed solution 1, and perform ultrasound for 30 minutes.

[0091] Step 4: Weigh 85 mg of TiCl4 and add it to mixed solution 1, and stir for 10 minutes to form mixed solution 2.

[0092] Step 5: Weigh 38 mg of MnCl2 and add it to mixed solution 2, and stir for 10 minutes to form mixed solution 3.

[0093] Step 6: Weigh 260 mg of RuCl3 and dissolve it in 30 ml of acetone solution, and stir evenly to form a uniform solution C.

[0094] Step 7: Slowly drop the mixed solution 3 obtained in step 5 into the uniform solution C obtained in step 6, and perform ultrasound for 30 minutes to form a mixed solution 4.

[0095] Step 8: The mixed solution 4 obtained in step 7 is placed into a reactor and hydroheated at 110° C. for 20 h.

[0096] Step 9: The solid product obtained in step 8 was washed four times by centrifugation with acetone, then filtered and dried at 60°C.

[0097] Step 10: Grind the solid product obtained in step 9 into fine powder, and then place it in a tube furnace at 900° C. for reduction and carbonization.

[0098] Step 11: Grind the above product into fine powder, place it in a muffle furnace and calcine it at 300°C for 60 minutes to obtain RuMnTiSnOx catalyst.

[0099] PEM water electrolysis performance test: weigh 100 mg of RuMnTiSnO x Prepare a slurry as the anode catalyst. Similarly, weigh 100 mg of Pt / C and prepare a slurry as the cathode catalyst. The anode catalyst equivalent is 2 mg / cm 2 , the cathode catalyst equivalent is 0.3mg / cm 2 The catalyst prepared above is made into a membrane electrode, deionized water is introduced into the anode and cathode respectively, and a suitable gradient voltage is applied to the electrolytic cell.

[0100] AEM water electrolysis performance test: weigh 100 mg of RuMnTiSnO xPrepare a slurry as the anode catalyst. Similarly, weigh 100 mg of Pt / C and prepare a slurry as the cathode catalyst. The anode catalyst equivalent is 6 mg / cm 2 , the cathode catalyst equivalent is 0.3mg / cm 2 The catalyst prepared above was made into a membrane electrode, 1 mol KOH solution was introduced into the anode and cathode respectively, and a suitable gradient voltage was applied to the electrolytic cell.

[0101] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A highly stable multi-component rutile structured acid / base amphoteric water electrolysis catalyst, characterized in that: The invention comprises the following components in parts by weight: 0.1 to 25 parts of a catalytically active non-noble metal precursor, 0.1 to 50 parts of a catalytically active noble metal precursor, 1 to 200 parts of an acetone solution and 1 to 200 parts of a metal chelating agent.

2. The highly stable multi-component rutile acid / base amphoteric water electrolysis catalyst according to claim 1, characterized in that: The catalytically active non-noble metal precursor is a variety of SnCl4, MnCl2, GeCl4, VCl3, WCl3 and TiCl4.

3. The highly stable multi-component rutile acid / base amphoteric water electrolysis catalyst according to claim 1, characterized in that: The catalytically active noble metal precursor is RuCl3 or H2IrCl6.

4. The highly stable multi-component rutile structured acid / base amphoteric water electrolysis catalyst according to claim 1, characterized in that: The metal chelating agent is one of phenanthroline, xanthate, dithiocarbamate derivatives, ethylenediaminetetraacetic acid, diethylenetriammonium pentaacetic acid, citric acid, and hexamethylenetetraammonium.

5. A method for preparing the highly stable multi-component rutile structured acid / base amphoteric water electrolysis catalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) uniformly mixing the acetone solution and the metal chelating agent to form a solution A; (2) uniformly mixing the acetone solution and the catalytically active non-noble metal precursor a to form a solution B; (3) slowly adding solution B dropwise into solution A, and after ultrasonic treatment, forming a mixed solution 1; (4) adding one or more catalytically active non-noble metal precursors b into the mixed solution 1 and stirring to form a mixed solution 2, wherein the catalytically active non-noble metal precursor a and the catalytically active non-noble metal precursor b are different substances in the catalytically active non-noble metal precursor; (5) dissolving a catalytically active noble metal precursor in an acetone solution and stirring the solution to form a solution C; (6) slowly adding the mixed solution 2 dropwise to the solution C, and after ultrasonic treatment, forming a mixed solution 3; (7) Adding the mixed solution 3 into a reaction kettle to carry out a hydrothermal reaction; (8) washing the solid product obtained in step (7) by centrifugation with acetone, and then filtering and drying; (9) grinding the solid product obtained in step (8) into fine powder, and then reducing and carbonizing it in a tube furnace; (10) Grinding the product obtained in step (9) into fine powder, and calcining at low temperature to obtain the acid / base amphoteric water electrolysis catalyst with multi-element high-stability rutile structure.

6. The method for preparing a highly stable multi-component rutile structured acid / base amphoteric water electrolysis catalyst according to claim 5, characterized in that: In step (3) and step (6), the ultrasonic time is 30 to 60 minutes; in step (4), the stirring time is 10 to 30 minutes.

7. The method for preparing a highly stable multi-component rutile structured acid / base amphoteric water electrolysis catalyst according to claim 5, characterized in that: In step (7), the temperature of the hydrothermal reaction is 110 to 180° C., and the time of the hydrothermal reaction is 15 to 24 hours.

8. The method for preparing a highly stable multi-component rutile structured acid / base amphoteric water electrolysis catalyst according to claim 5, characterized in that: In step (8), the drying temperature is 40 to 80°C.

9. The method for preparing a highly stable multi-component rutile structured acid / base amphoteric water electrolysis catalyst according to claim 5, characterized in that: In step (9), the temperature of the tube furnace is 850-900°C.

10. The method for preparing a highly stable multi-component rutile structured acid / base amphoteric water electrolysis catalyst according to claim 5, characterized in that: In step (10), the calcination temperature is 200-300° C. and the calcination time is 30-60 min.

Citation Information

Patent Citations

  • Nano-catalyst with core-shell structure, preparation method and application

    CN117878342A

  • Antipolar proton exchange membrane fuel cell catalyst with high CO poisoning resistance and high resistance and preparation method of antipolar proton exchange membrane fuel cell catalyst

    CN118073580A

  • Ultrafine particle of rutile-type titanium oxide

    KR1020070031441A